2018
DOI: 10.3390/toxics6020032
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Exposure Disrupts Periodontal Bone in Experimental Animals: Implications for Periodontal Disease in Humans

Abstract: Cadmium (Cd) is an environmental contaminant that damages the kidney, the liver, and bones. Some epidemiological studies showed associations between Cd exposure and periodontal disease. The purpose of this study was to examine the relationship between Cd exposure and periodontal disease in experimental animals. Male Sprague/Dawley rats were given daily subcutaneous injections of Cd (0.6 mg/kg/day) for up to 12 weeks. The animals were euthanized, and their mandibles and maxillae were evaluated for levels of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Whole-blood and urinary Cd concentrations are widely accepted markers of Cd exposure and accumulation [ 14 , 18 ]. Long-term exposure to Cd has been associated with various conditions, including various renal syndromes, osteoporosis and osteomalacia, CVD, and different types of cancer [ 14 , 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Its endocrine-disrupting properties have also been shown, suggesting its possible effects on estrogenic activity [ 26 , 27 , 28 , 29 ], alterations in semen and the testis [ 30 , 31 , 32 ], and a role in thyroid disorders [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whole-blood and urinary Cd concentrations are widely accepted markers of Cd exposure and accumulation [ 14 , 18 ]. Long-term exposure to Cd has been associated with various conditions, including various renal syndromes, osteoporosis and osteomalacia, CVD, and different types of cancer [ 14 , 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Its endocrine-disrupting properties have also been shown, suggesting its possible effects on estrogenic activity [ 26 , 27 , 28 , 29 ], alterations in semen and the testis [ 30 , 31 , 32 ], and a role in thyroid disorders [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the literature shows several studies relating the prevalence of periodontal disease to exposure to environmental Cd (for a review, see [10]), this is the first study to examine the bioaccumulation of Cd in the human mandible. Cd bone levels found in human mandible samples were in a similar range to Cd levels found in transilliac bone biopsies on patients with end-stage renal disease [13].…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that Cd exposure is associated with periodontal disease. However, there are conflicting epidemiological studies that show or fail to show a connection between Cd and periodontal disease (for a review, see [10]). We have recently published a report showing that Cd causes loss of alveolar bone in a rodent model of long-term Cd poisoning [10].…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviation: GABA: g-amino butyric acid. (Kasuya et al, 1992;Buha et al, 2017;Tinkov et al, 2017;Browar et al, 2018 (Siegel et al, 1988) 2019). A recent analysis of 25 CBD oil products purchased in Mississippi, of the 25 products, only 3 were within ±20% of label claim, 15 were below the stated claim for CBD, 2 exceed these claims by more than 50%, and THC content for 3 products exceeded the 0.3% legal limit (Gurley et al, 2020).…”
Section: Labeling Inaccuracymentioning
confidence: 99%
“…It has also been shown that application of phosphate fertilizers targeted for Cannabis growth increases the uptake of cadmium by Cannabis when grown in cadmium contaminated soils though the mechanism is not yet clear (Singani and Ahmadi, 2012). Currently, no cases of cadmium contaminated Cannabis causing health problems are found in the literature; however, there are several diseases that have been associated with exposure to cadmium through smoking and diet including periodontal disease (Browar et al, 2018), pancreatic cancer (Buha et al, 2017), and diabetes (Tinkov et al, 2017). Most severely, chronic exposure causes Itai-Itai disease, which is characterized by intense bone pain, a disrupted gait, and numbness in all extremities (Kasuya et al, 1992).…”
Section: Cadmiummentioning
confidence: 99%